Analytical modeling of the dynamic thermal behavior of stabilized compacted earth blocks walls for bioclimatic constructions - Mahdad, M’hamed; Hammas, Aghiles; Abboudi, Said (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The main challenge in bioclimatic constructions using compressed and stabilized earth blocks (CSEB) is determining the optimal external wall thickness to ensure good thermal comfort. This study investigates heat transfer through opaque walls made with various CSEB samples commonly used in Algeria, using the cyclic admittance method. Five homogeneous CSEB materials were evaluated based on several dynamic thermal parameters: admittance (Y), transmittance (U), surface factor (F), decrement factor (DF), and time lag (TL). Results showed that walls made with CSEB-2 material at 40 cm thickness had the best thermal performance. Additionally, multiple linear regression (MLR) analysis was applied to predict TL and U values, yielding high coefficients of determination (R² of 0.98 and 0.79, respectively). The study concluded that TL and U values are strongly influenced by wall thickness and the compaction energy of the CSEB samples.